Pengaruh Alokasi Pendapatan Asli Daerah terhadap Perubahan Anggaran Belanja Langsung Pemerintah Kabupaten Brebes pada Masa Pandemi Covid-19 - Suci Alfiani; Anisa Sains Kharisma; Yenny Ernitawati; Amelia Sholeha; Nasiruddin (Journal of Accounting and Finance (JACFIN), 2020)
During the COVID-19 pandemic, all institutions experienced a great impact, including the budget. The purpose of this research is to determine the amount of Regional Original Income (PAD) for budget changes set by the Brebes Regency Government during the pandemic. The research method uses qualitative. The research sample of one unit of analysis in a related field, namely the budget field at the Brebes Regency Office of the Regional Revenue, Financial Management and Assets Agency (BPPKAD) was obtained using in-depth interview techniques. The results showed that there was a positive influence of budget changes on the direct expenditure budget during the Covid-19 pandemic on the Brebes Regency Government.